2023
DOI: 10.1002/chem.202203369
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Intrinsically Disordered Regions in Transcription Factors

Abstract: Eukaryotic transcription factors (TFs) are the final integrators of a complex molecular feedback mechanism that interfaces with the genome, consolidating information for transcriptional regulation. TFs consist of both structured DNAbinding domains and long intrinsically disordered regions (IDRs) embedded with motifs linked to transcriptional control. It is now well established that the dynamic multifunctionality of IDRs is the basis for a wide spectrum of TF functions necessary to navigate and regulate the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 191 publications
0
19
0
Order By: Relevance
“…On the face of it, the high evolutionary rate of changes in the amino acid sequence in p53TAD, evident from the comparison of different extant tetrapods (Figure S6), is hard to reconcile with its interactions with both MDM2 and CBP/p300, and the centrality of p53 as a pleiotropic hub protein involved in multiple pathways (Levine, 2020). However, recent studies have shown that the exact sequence of TADs are often not crucial for binding coactivators as long as key elements are present in the binding motif, in particular hydrophobic residues (Trp, Leu) separated by negatively charged Asp or Glu (Zarin et al, 2017; Sanborn et al, 2021; Staller et al, 2022; Már et al, 2023). It has also been shown that hub proteins such as p53 that connect different biological “modules” (intermodule hubs) are generally less constrained and evolve faster than hub proteins regulating a specific biological process (intramodule hubs).…”
Section: Discussionmentioning
confidence: 99%
“…On the face of it, the high evolutionary rate of changes in the amino acid sequence in p53TAD, evident from the comparison of different extant tetrapods (Figure S6), is hard to reconcile with its interactions with both MDM2 and CBP/p300, and the centrality of p53 as a pleiotropic hub protein involved in multiple pathways (Levine, 2020). However, recent studies have shown that the exact sequence of TADs are often not crucial for binding coactivators as long as key elements are present in the binding motif, in particular hydrophobic residues (Trp, Leu) separated by negatively charged Asp or Glu (Zarin et al, 2017; Sanborn et al, 2021; Staller et al, 2022; Már et al, 2023). It has also been shown that hub proteins such as p53 that connect different biological “modules” (intermodule hubs) are generally less constrained and evolve faster than hub proteins regulating a specific biological process (intramodule hubs).…”
Section: Discussionmentioning
confidence: 99%
“…S6), is hard to reconcile with its interactions with both MDM2 and CBP/p300, and the centrality of p53 as a pleiotropic hub protein involved in multiple pathways (56). However, recent studies have shown that the exact sequence of transactivation domains are often not crucial for binding coactivators as long as key elements are present in the binding motif, in particular hydrophobic residues (Trp, Leu) separated by negatively charged Asp or Glu (57)(58)(59)(60). It has also been shown that hub proteins such as p53 that connect different biological "modules" (intermodule hubs) are generally less constrained and evolve faster than hub proteins regulating a specific biological process (intramodule hubs) (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Acting as hubs in PPI networks, the biological functions of IDPs significantly diverge from those of their ordered counterparts. IDPs are predominantly engaged in signal regulation 15,16 and gene transcription regulation, 17,18 while ordered proteins are primarily involved in catalysis and transport. Transcription factors 17,122 exemplify the role of disordered proteins.…”
Section: Interactions Of Idps With Other Biological Moleculesmentioning
confidence: 99%
“…The dynamic structural characteristics of IDPs present several benefits, 14 including high flexibility, high specificity with low affinity binding, and easy regulation through posttranslational modifications (PTMs). These attributes lay the foundation for their ubiquitous involvement in signal transduction and transcription regulation processes across archaea, bacteria, plant, and animal cells 15–18 …”
Section: Introductionmentioning
confidence: 99%